Boundaries of management performance measures (MPMs) disclosed in primary financial statements prepared in accordance with new standard planned to supersede IAS 1 - Ewa Wanda Maruszewska; Maciej Andrzej Tuszkiewicz (Central European Economic Journal (CEEJ), 2024)
We outline the management performance measures (MPMs)' boundaries based on the upcoming introduction of MPM's definition to International Financial Reporting Standards (IFRS). The literature investigates business performance measures concentrating on managers' needs, while IFRS aims to provide financial information to external users who provide resources to the entity. This indicates a gap between how performance metrics have been investigated so far and how IFRS will adopt them. We used analysis of the exposure draft of the planned standard together with working materials developed in the consultation process. Further, a case study is presented. Results show that the scope of MPM to be introduced to IFRS is limited compared to the broad spectrum of performance measures presented in the literature. We contribute by showing the avenues for future performance measures research using signalling and agency theory and by indicating the limited scope of MPMs and thus bound prospects for using them for a full assessment of the entity's performance.
Keywords: M00; M40; M41; 330; Keywords; management performance measures; MPM; performance measurement; IAS 1; IFRS 18; signalling theory; agency theory